In Vitro Antimicrobial Activity of Garlic (Allium Sativum) Against Clinical Isolates of Vibrio Cholerae - Muhammad Bilal , Abdul Rauf,Farhan Rasheed , Qasim Shahzad Butt , Aadil Hussain , Zubair Mehboob , Malik Siddique Mehmood (Journal of Rawalpindi Medical College, 2016)
Introduction: To study the in vitro antimicrobial activity of garlic (Allium Sativum) against clinical isolates of Vibrio Cholerae Methods: Thirty three clinical isolates of V. cholerae were evaluated for their susceptibility to aqueous extract of Pakistani and Chinese garlic. ATCC strain of P. aeruginosa (ATCC 27853) was used as the standard control strain. The cloves were peeled and blended (50 gm) in 90 ml of distilled water in separate blenders. The extracts were sterilized by gamma radiation. Aqueous extracts of Pakistani and Chinese garlic were tested in triplicate. Quantitative analysis of Pakistani and Chinese garlic aqueous extracts was done. As the extracts of both types of Pakistani and Chinese garlic exhibited inhibitory effect against test strain of V. cholerae, aqueous extracts were further evaluated in agar dilution assay to determine MIC against thirty three clinical isolates of V. cholerae and one ATCC reference strain. Results: The zones of inhibition measured by using agar well diffusion assay were 28.12 mm and 32.14 mm for Pakistani and Chinese garlic aqueous extracts respectively. All the isolates were inhibited at concentration of 8.66 mg/mL by Chinese garlic and at 10 mg/mL by Pakistani garlic aqueous extract. Conclusion: Natural sources, like garlic extracts , may be an effective alternative, to resistant strains of vibrio cholera.